Adenoviruses from Human Immunodeficiency Virus-Infected Individuals, Including Two Strains That Represent New Candidate Serotypes Ad50 and Ad51 of Species B1 and D, Respectively - De Jong, Jan C. (American Society for Microbiology, 1999)
Adenovirus (Ad) isolates from a large number of human immunodeficiency virus (HIV)-infected individuals were compared serologically and genetically with Ad isolates from immunocompetent patients. Between 1982 and 1994, stool and urine samples from 137 subjects with AIDS hospitalized in The Netherlands yielded 143 Ad strains. Forty additional Ad strains were obtained from 35 HIV-positive patients in Manchester, United Kingdom, in 1992 and 1993. Of these 183 HIV-associated Ad strains, 84% belonged to species D and 3% belonged to species C. These strains were compared with 2,301 Ad strains collected during general diagnostic examinations in The Netherlands from 1973 to 1992. Of the latter strains, 5% belonged to species D and 49% belonged to species C. Two of the Ads isolated from fecal specimens of AIDS patients represent new serotypes: candidate Ad serotype 50 (prototype strain, Wan) of subspecies B1 and candidate Ad serotype 51 (prototype strain, Bom) of species D. The DNA restriction enzyme patterns of strains Wan and Bom differed from the patterns of all established prototypes.